2015
DOI: 10.3390/foods4030400
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the Encapsulation of an Aqueous Bitter Melon Extract by Spray-Drying

Abstract: Our aim was to optimise the encapsulation of an aqueous bitter melon extract by spray-drying with maltodextrin (MD) and gum Arabic (GA). The response surface methodology models accurately predicted the process yield and retentions of bioactive concentrations and activity (R2 > 0.87). The optimal formulation was predicted and validated as 35% (w/w) stock solution (MD:GA, 1:1) and a ratio of 1.5:1 g/g of the extract to the stock solution. The spray-dried powder had a high process yield (66.2% ± 9.4%) and high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
3
32
2
1
Order By: Relevance
“…If some of the moisture remains inside the nanocapsules, their structure changes from smooth to intense and rough state (Tonon, Brabet, & Hubinger, 2008). Tan, Kha, Parks, Stathopoulos, and Roach (2015) showed a similar morphology of the melan extracts in nanocapsules of maltodextrin and arabic gum coatings.…”
Section: Morphology Of Nanocapsulesmentioning
confidence: 94%
“…If some of the moisture remains inside the nanocapsules, their structure changes from smooth to intense and rough state (Tonon, Brabet, & Hubinger, 2008). Tan, Kha, Parks, Stathopoulos, and Roach (2015) showed a similar morphology of the melan extracts in nanocapsules of maltodextrin and arabic gum coatings.…”
Section: Morphology Of Nanocapsulesmentioning
confidence: 94%
“…It was also shown that the microcapsules with surface dents occupied a large proportion. Many studies had confirmed that the drying temperature taken an important effect on the morphology of microcapsules (Janiszewska & Witrowa-Rajchert, 2009;Mestry, Mujumdar, & Thorat, 2011;Nijdam & Langrish, 2006;Tan et al, 2015;Tonon, Brabet, & Hubinger, 2008). At high drying temperatures, the moisture of the particles evaporated quickly, resulting to most of particles having a smooth and hard outer shell.…”
Section: Properties Of Microcapsulesmentioning
confidence: 99%
“…However, its high cost, limited supply, has restricted the use of GA. Maltodextrin (MD) can ameliorate the oxidation resistance of encapsulated oil but have the disadvantage of poor emulsion stability and low microencapsulation efficiency (ME) (Gharsallaoui, Saurel, & Chambin, 2012). The combination of GA and MD had been applied to the encapsulation of bitter melon extract (Tan, Kha, Parks, Stathopoulos, & Roach, 2015), soy oil (McNamee, O’Riordan, & O’Sullivan, 2001), fatty acids (Minemoto, Hakamata, Adachi, & Matsuno, 2002), and flavor (Apintanapong & Noomhorm, 2003). These results had shown that the combination of GA and MD could give play to their respective characteristics and make up each other's shortcomings, which reduced costs and improved product quality.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the influences of different temperatures on the quality of spray-dried mulberry juice powder, the mulberry juice was mixed with maltodextrin and gum Arabic at the ratio of 7:3 (w/w) [32] and then spray-dried with the constant feed flow rate of 8 rpm at different temperatures (120 • C, 130 • C, 140 • C and 150 • C, 160 • C), as described by Fazaeli et al [11] with slight modification.…”
Section: Study On Effects Of Temperaturesmentioning
confidence: 99%